What are the limits? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Residues of some veterinary drugs in animals and food: Cefuroxime sodium; Cypermethrin; a-Cypermethrin; Dihydrostreptomycin and streptomycin; Ivermectin; Lincomycin; Melengestrol acatate; Oxytetracyline; Phoxim.